PENGARUH PENINGKATAN LIPOFILISITAS PADA SENYAWA ANALOG UK-3A DALAM MENGHAMBAT PERTUMBUHAN SEL KANKER P-388 - Hanafi M; Y Anita; AMJ. Putra; A. Darmawan; N. Artanti; Linar Z. Udin (Jurnal Kimia Terapan Indonesia, 2009)
Antibiotic UK-3A contains a 9-membered dilactone ring. It had been isolated as a minor component from the mycelium of 5trepyomyces sp. 51701.The antibiotic was hypothesized to be potential to inhibit the growth of leukemia cancer cell line of P388 and KB with ICso 38 and 20 Dg/mL, respectively. To understand the effect of lipophilicity increase of the analogues on their anticancer activities based on QSAR parameter (Log P) and binding energy to BcL-xL protein. To produce analogues of UK-3A, 3hydroxypicolinyl serine methyl ester (A) was synthesized from 3-hydroxypicolinic acid and L-serine methyl ester. The product was then esterified by pentanoic (1), hexanoic (2), heptanoic (3), and octanoic (4). The final products were confirmed with IHand 13C FT-NMR and FTIR spectra, and also MS spectra. Then they were tested against P388 Murine Leukemia cells. The result of bioassay showed lipophilicity increase of3hydroxypicolinyl serine methyl octhyl ester (PSMOE) correlated positively with their anticancer activity increase, withICso 15.4mg/mL against P388 cell lines.Keywords: Anticancer, Streptomyces sp 517-02, UK-3A, Analog UK-3A and P388